Pembuatan Aplikasi Pengarsipan Surat Berbasis Macro VBA Excel pada Kantor Kecamatan Tenggarong Seberang - Achmad Nur Saleh; Rahmat Rahmat; Muhammad Taufiq Sumadi (Politeknik Kampar, 2023)
Tenggarong Seberang District is one of the agencies under the auspices of the Kutai Kartanegara Regency Government which still uses a correspondence system as a means of official communication or assignment. The large number of incoming letters or outgoing letters in Tenggarong Seberang District, of course, currently requires a system that can facilitate and assist the letter archiving process. In Tenggarong Seberang Subdistrict, letter filing is still done manually, sometimes when you want to find a letter data and letters that have been stored for a long time in a warehouse or letter storage box are difficult to find because they are stacked with other letters and even the letters you are looking for are often lost. So after analyzing the Tenggarong Seberang District, it is planned to make an archiving application that can store data properly and safely. The letter archive application created will use the Macro VBA Excel system to manage the inputted archives. This research method uses the DSRM method which consists of 6 stages, namely Problem Identification and Motivation, Define the Objectives for a Solution, Design and Development, Demonstration, Evaluation, Communication. To get a solution to this problem is to create a Macro VBA Excel-based Mail Archive system to store mail data safely and easily.